Individual-based creatine kinase reference values in response to soccer match-play - Ribeiro, J.; Gantois, P.; Moreira, V.; Miranda, F.; Romano, N.; Nakamura, F. Y. (International Journal of Sports Medicine, 2022)
The aim of the present study was to determine the creatine kinase reference limits for professional soccer players based on their own normal post-match response. The creatine kinase concentration was analyzed in response to official matches in 25 players throughout a 3-year period. Samples were obtained between 36-43 hours following 70 professional soccer matches and corresponded to 19.1±12.1 [range: 6-49] samples per player. Absolute reference limits were calculated as 2.5th and 97.5th percentile of the samples collected. Creatine kinase values were also represented as a percentage change from the individual`s season mean and represented by 90th, 95th and 97.5th percentiles. The absolute reference limits for creatine kinase concentration calculated as 97.5th and 2.5th percentiles were 1480 U.L-1 and 115.8 U.L-1, respectively. The percentage change from the individual`s season mean was 97.45±35.92% and players were in the 90th, 95th and 97.5th percentiles when the percentages of these differences were 50.01, 66.7, and 71.34% higher than player`s season mean response, respectively. The data allowed us to determine whether the creatine kinase response is typical or if it is indicative of a higher than normal creatine kinase elevation and could be used as a practical guide for detection of muscle overload, following professional soccer match-play.